Course of pregnancy and labor in women with type 2 diabetes mellitus and obesity - Galina A. Batrak; Nataliya V. Batrak (LLC "MEDIAFORMAT", 2024)
Maternal diabetes is associated with pregnancy complications and increased rates of adverse maternal and neonatal outcomes. Short-term complications include macrosomia, large for gestational age, respiratory distress syndrome, neonatal hypoglycemia, neonatal intensive care unit admission, fetal growth restriction, congenital anomalies, preterm birth, preeclampsia, operative delivery, while in the long term both mothers and their infants have an increased risk of metabolic diseases. The results of the conducted scientific study confirm that type 2 diabetes and obesity are closely associated with pregnancy complications: early and late threatened miscarriage, cervical insufficiency, hyperemesis gravidarum, anemia, chronic and gestational hypertension, moderate and severe preeclampsia, premature detachment of a normally located placenta, placental insufficiency, fetal growth retardation syndrome, pathological and insufficient weight gain, diabetic fetopathy of the fetus in the form of macrosomia, double contour of the fetal head/trunk, hepatomegaly, splenomegaly, pyelectasis of the fetal kidneys, congenital malformations of the fetus, intrauterine fetal death, prenatal rupture of membranes, clinically narrow pelvis, operative delivery, premature birth and, as a result, a low assessment of the newborn on the Apgar scale at 1 and 5 minutes.